Зародження чернечого самітництва в Галлії у V ст. (на прикладі «Vita Patrum Jurensium») (І) - Боднарюк, Б.М. (My University, 2008)
SummaryB. Bodnariuk. Formation of the monastic anchoret in Gallia in the V с. (on example «Vita Patrum Jnrensium») (I)This article deals with questions connected with the process of the appearing and formation of Christian monastic anchoret on the territory of Gallia in the V c. Besides that, the author analyses the peculiarities and characteristic features of ascetic practice of the first Gallian anachorets, using the facts contained in the «Living of Jurassic Paters».
Помилково вказано прізвище автора Бондарюк.